2020
DOI: 10.3390/en13184887
|View full text |Cite
|
Sign up to set email alerts
|

Design of Battery Storage System for Malaysia Low Voltage Distribution Network with the Presence of Residential Solar Photovoltaic System

Abstract: The recent proliferation of residential solar photovoltaic systems has prompted several technical challenges to the operation of low voltage (LV) distribution networks. More specifically, the mismatch of the solar generation and demand profiles, particularly during the midday when the demand is low and solar generation is high, can lead to network overvoltages and increased network losses. In addition, the solar photovoltaic system is not able to reduce the system’s maximum demand, given the residential LV net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study by [116] proposed two designs of an energy storage system with PV solar cells to investigate the effects of mismatch between solar generation and demand profiles. They found that the PV generation strategy (PVGS) whereby the energy storage system is charged completely based on the total amount of PV-generated power could provide technical benefits to the system and is more cost-effective.…”
Section: Solar Energy Generation and Storage Capacity Mismatchmentioning
confidence: 99%
“…A study by [116] proposed two designs of an energy storage system with PV solar cells to investigate the effects of mismatch between solar generation and demand profiles. They found that the PV generation strategy (PVGS) whereby the energy storage system is charged completely based on the total amount of PV-generated power could provide technical benefits to the system and is more cost-effective.…”
Section: Solar Energy Generation and Storage Capacity Mismatchmentioning
confidence: 99%
“…Besides that, ESS can also be utilized to support the essential supply of electricity immediately when a blackout happens [26], [27]. Besides, the characteristics of the ESSs, which are able to optimize the output from renewable sources, have driven the application of ESSs with renewable energy to solve the power shortage problem [28]- [30]. The reliability of the power supply is improved by utilizing solar and wind power generation integrated with batteries [26], [31].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is also one of the best way to drive maximum electricity and minimize losses, which make the total system simple, cost effective, and efficient. [11][12][13][14][15][16] In 2019 end, global grid-connected and off grid photovoltaic (PV) devices solar capacity reached to 627 GW and 3.4 GW, respectively. 17 Also, solar module pricing demonstrates Moore's law moving from $300/watt in 1956, $10/ watt in the 1990 s, $1.12/watt in 2019, and $ 1.08/watt today.…”
mentioning
confidence: 99%